2012
DOI: 10.1093/cid/cis968
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions Between the Hepatitis C Virus Protease Inhibitor Boceprevir and Ritonavir-Boosted HIV-1 Protease Inhibitors Atazanavir, Darunavir, and Lopinavir

Abstract: Concomitant administration of boceprevir with PI/r resulted in reduced exposures of PI and boceprevir. These drug-drug interactions may reduce the effectiveness of PI/r and/or boceprevir when coadministered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 17 publications
2
52
0
2
Order By: Relevance
“…Recently, drug interactions between BOC and several ritonavirboosted HIV protease inhibitors (atazanavir, lopinavir, darunavir) have been reported (Hulskotte et al, 2012a). Unexpectedly, the exposure of all agents (BOC, HIV agents, and ritonavir) was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, drug interactions between BOC and several ritonavirboosted HIV protease inhibitors (atazanavir, lopinavir, darunavir) have been reported (Hulskotte et al, 2012a). Unexpectedly, the exposure of all agents (BOC, HIV agents, and ritonavir) was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, telaprevir should not be coadministered with ritonavir-boosted darunavir, fosamprenavir, or lopinavir, 92 and boceprevir is not recommended for use with any boosted protease inhibitor. 93 Concentrations of boceprevir are significantly reduced in the presence of efavirenz, and this combination should be avoided. 94 Similarly, telaprevir concentrations are reduced by concomitant efavirenz; the possibility of using higher telaprevir doses to overcome this interaction is being explored.…”
Section: Hepatitis Cmentioning
confidence: 99%
“…The protease inhibitor BOC decreased the exposure of all protease inhibitors; ATV/ritonavir did not significantly affect BOC exposure, whereas BOC was reduced by 45% and 32% when co-administered with LPV/ritonavir and DRV/ritonavir, respectively [75] . In a recent study no significant drug interaction between BOC and raltegravir was found in healthy volunteers [76] .…”
Section: Art Management In Hiv/hcv Coinfected Patients During Treatmementioning
confidence: 85%